Formative Assessment Practiced in Higher Education: Lecturers’ and Students’ Perceptions - Achmad Taqlidul Chair Fachruddin; Ahmad Ardillah Rahman (Eduvelop: Journal of English Education and Development, 2026)
Discrepancies between lecturers’ and students’ perceptions of formative assessment can weaken instructional alignment and reduce learning effectiveness in higher education. This study aimed to (1) describe formative assessment practices at STAIN Majene and (2) compare lecturers’ and students’ perceptions across five dimensions: learning objectives, monitoring, feedback, self-assessment, and peer assessment. Using a descriptive quantitative, cross-sectional design, questionnaire data were collected from 20 lecturers and 250 odd-semester students at STAIN Majene. The instrument consisted of 25 items and demonstrated acceptable internal consistency across dimensions, with combined Cronbach’s alpha coefficients ranging from .70 to .83. Descriptive findings revealed that lecturers rated learning objectives (M = 4.38, SD = 0.533) and monitoring (M = 4.02, SD = 0.536) more positively, while students rated feedback most highly (M = 4.40, SD = 0.554). Inferential analysis using Welch’s independent-samples t test showed significant differences in learning objectives, t(21.71) = 8.115, p < .001, and feedback, t(24.51) = -10.289, p < .001, while monitoring and peer assessment did not differ significantly. Self-assessment showed a smaller difference at the .05 level, t(24.51) = -2.374, p = .026. Overall, the findings suggest that formative assessment at STAIN Majene remains stronger in lecturer-led practices than in learner-activating dimensions, particularly peer assessment. As an institutional study situated in a state Islamic higher education context in West Sulawesi, this research contributes empirical evidence on lecturer–student perceptual gaps and offers directions for strengthening learning objective transparency, sustaining effective feedback, and systematizing self- and peer-assessment practices.